WYBRANE ZAGADNIENIA RELACJI RELIGIA-KOŚCIÓŁ-PAŃSTWO-PRAWO W STANACH ZJEDNOCZONYCH - Lewicki, Zbigniew (Zeszyty Prawnicze, 2016)
SELECTED ASPECTS OF THE INTERRELATIONSHIP BETWEEN CHURCH, STATE, RELIGION, AND THE LAW IN THE UNITED STATES Summary The United States is a secular state which at the same time puts religion and its institutions at the centre of its legal and constitutional considerations. This situation leads to frequent tension between state institutions and the followers of different religions, whose religious requirements or prohibitions come into conflict with the uniform legal standards. The classic examples of this include Mormon polygamy, which Mormons consider a condition of salvation, but which has been found unconstitutional; and the use of legally prohibited drugs by the followers of Indian religions during their religious ceremonies. Recognition of the needs of worshippers in the latter case shows that over time the U.S. authorities have tended more and more to acknowledge the need to take into account the specific requirements of the non-mainstream religious institutions. Another specific feature of the U.S. system of constitutional law is that as a rule such discrepancies are settled not by Congress but by the Supreme Court, although the two institutions have been known to make conflicting decisions on the same issue. The article is also a review of judicial decisions and legislative acts on controversial issues like abortion, the admissibility of the use of stem cells, same-sex marriages, and conscientious objection to military service.